Improving The Quality of Sanitation in The Popcorn Production Process at UMKM Ziqma Production: Peningkatan Kualitas Sanitasi pada Proses Produksi Popcorn di UMKM Ziqma Production - andre yusuf trisna putra; Muhammad Alfid Kurnianto (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2024)
Ziqma Production is an Micro, Small Medium Enterprise (MSME) that produces snacks with a superior product, popcorn. The pop corn production process at Ziqma is still simple and does not yet implement quality control management and food safety. Therefore, the aim of this activity is to provide education about implementing sanitation to improve the quality of the production process. This program was implemented on August 3 2023. The activities consist of three stages, namely coordination with partner, counseling about CPPOB principles, and implementation of the use of production sanitation equipment according to Cara Produksi Pangan Olahan yang Baik (CPPOB) principles. The result of this activity is that Zigma workers know the theory about sanitation. Apart from that, be able to use sanitary equipment, such as aprons, masks, gloves and head coverings. It is hoped that after this activity, all workers can implement sanitation so that the quality of popcorn products can be maintained.